Understanding our environment : an introduction to environmental chemistry and pollution - Harrison, Roy M., 1948- (Royal Society of Chemistry, 1999)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. As an introductory text aimed at those having little background knowledge of the field and requiring only a modest background in science, Understanding our Environment is unparalleled. This third edition enhances the standing of the title by developing a more international approach. Bridging all the important environmental media such as the atmosphere, fresh waters, oceans and solid earth, it also emphasises the inter-linkages between these media. The major human and environmental impacts of pollution are summarised, and case studies are included as illustrations of the measures needed for control. Worked examples and questions are included to facilitate both teaching and learning of the subject. This book will be essential reading for students in environmental science and related areas, as well as scientists and engineers in industry, public service and consultancy who require a basic understanding of environmental processes.
Previous edition: 1992.
Keywords: Pollution.; Environmental chemistry.; elektronické knihy; electronic books